Diabetic retinopathy - Salam, Adzura; Wolf, Sebastian; Framme, Carsten (Wiley-VCH, 2012)
This new handbook covers the world of biophotonics not only geographically -- with the editors coming from different continents -- but also in terms of content, since the authors come from the whole spectrum of biophotonic basic and applied research. Designed to set the standard for the scientific community, these three volumes break new ground by providing readers with the physics basics as well as the biological and medical background, together with detailed reports on recent technical advances. The Handbook also adopts an application-related approach, starting with the application and then citing the various tools to solve the scientific task, making it of particular value to medical doctors. Divided into several sections, the first part offers introductory chapters on the different fields of research, with subsequent parts focusing on the applications and techniques in various fields of industry and research. The result is a handy source for scientists seeking the basics in a condensed form, and equally a reference for quickly gathering the knowledge from neighboring disciplines. Absolutely invaluable for biophotonic scientists in their daily work.